2018
DOI: 10.1159/000490172
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Orexin/Hypocretin System in the Brain of Holostean Fishes: Assessment of Possible Relationships with Monoamines and Neuropeptide Y

Abstract: Holosteans form a small group of actinopterygian fishes considered the sister group of teleosts. Despite this proximity to the biggest group of vertebrates, relatively few studies have been conducted to investigate the organization of the central nervous system of this group of fishes. In this study, the neuroanatomical distribution of orexin/hypocretin-like immunoreactive (OX-ir) cell bodies and fibers was analyzed in the brain of 3 representative species of the 2 orders of extant holosteans, the spotted gar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…The localization of the Isl1-ir cell populations detected in the present study was framed within the neuromeric model (Puelles & Rubenstein, 2003, adapted for the brains of nonteleost actinopterygian fishes, and is summarized in sagittal schematic drawings of the three groups of fishes (Figures 3a, 4a The nomenclature used is essentially the same followed in previous studies of the brain in nonteleost actinopterygian fishes (González et al, 2014;Jiménez et al, 2020;López et al, 2013López et al, , 2014López et al, , 2016López et al, , 2019López et al, , 2022Lozano et al, 2018Lozano et al, , 2019Lozano et al, , 2020Morona et al, 2013).…”
Section: Evaluation and Presentation Of The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The localization of the Isl1-ir cell populations detected in the present study was framed within the neuromeric model (Puelles & Rubenstein, 2003, adapted for the brains of nonteleost actinopterygian fishes, and is summarized in sagittal schematic drawings of the three groups of fishes (Figures 3a, 4a The nomenclature used is essentially the same followed in previous studies of the brain in nonteleost actinopterygian fishes (González et al, 2014;Jiménez et al, 2020;López et al, 2013López et al, , 2014López et al, , 2016López et al, , 2019López et al, , 2022Lozano et al, 2018Lozano et al, , 2019Lozano et al, , 2020Morona et al, 2013).…”
Section: Evaluation and Presentation Of The Resultsmentioning
confidence: 99%
“…We have observed the expression of NPY in neurons of the Tu of cladistian and holostean fishes in previous works (López et al, 2014;Lozano et al, 2018), and the presence of somatostatin, NPY, GHRH, and POMC, among other neuropeptides, has been reported in the hypothalamus of the Chinese sturgeon (Xie et al, 2022). Finally in the basal hypothalamus, the double labeling of Isl1 and TH, observed in some cells of the tuberal hypothalamus of nonteleost actinopterygian fishes, has not been reported in teleost fishes (Baeuml et al, 2019), or in any other vertebrate studied, being an exclusive feature of these groups of fishes.…”
Section: Forebrainmentioning
confidence: 93%
See 1 more Smart Citation
“…Immunohistochemical studies have reported the expression of 5-HT 1A receptors in trigeminal motor nuclei and surrounding areas during the neonatal period [53]. The colocalization of 5-HT receptor subtypes and Ox has been analyzed in the hypothalamus, posterior tubercle, thalamus, and mesencephalic tectum using immunofl uorescence [54,55], but colocalization has not yet been reported in trigeminal neurons. In the present study, Ox-A enhanced bursting activities, accompanied by increased burst duration and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Hence attempt has been made to convey the updates on dopamine in the brain of fishes. Abundant orexinergic fibers and terminals have been observed interspersed with the TH-ir cells of the POA and hypothalamus in the L. oculatus (Lozano et al, 2018) [28] suggests the collective role of peptides in the reproduction. Super fused POA slices treated with a NPY Y 2 -receptor agonist, NPY 13-36 resulted in a significant reduction in THimmunoreactivity in NPPa and demonstrated that DA and NPY interacts in NPPa to regulate the LH release (Kumar et al, 2014) [24] .…”
Section: Introductionmentioning
confidence: 99%